An Analysis of the Feasible Entry Mode for Tottenham Hotspur’s Entry into China - Zhang, Lei (2013)
An increasing number of European football clubs has developed global strategies with an emphasis on the Chinese market, which seems to be a shortcut to their global success. In order to achieve an effective expansion, the selection of appropriate entry modes should be conducted cautiously. This paper aims to select feasible entry modes for Tottenham Hotspur F.C., an emerging power in the Premier League, to enter into the Chinese market.